2015
DOI: 10.17718/tojde.94170
|View full text |Cite
|
Sign up to set email alerts
|

Using Space in Social Media to Promote Undergraduate Students’ Critical Thinking Skills

Abstract: The current study was conducted to see the effectiveness of using social media to enhance students' critical thinking skills. To fulfill the purpose of the study, a 14-week experimental study was performed with two groups of students. Both groups were introduced to how to respond to questions based on Revised Bloom's Taxonomy. During the period of doing the activity, students in the experimental group had to post answers in Facebook and got feedback from peers and teacher as mutual learning while those in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
6
19
2
1
Order By: Relevance
“…Critical thinking was found to increase both in an EFL class offered in a traditional setting, but much more so in a Facebook-enhanced one (dppc2 = 0.545) (Morris, 2008), after students were trained to answer questions developed on a revised Bloom's Taxonomy scale (Pattanapichet & Wichadee, 2015). Installing courseware in the laboratory to enhance teacher-centered instruction, led students in the study by Tsai (2012) to develop more critical thinking skills in the sense that they reported to have improved "abilities of thinking, analysis and problem-solving" (p. 56).…”
Section: Cognitive Engagement and Educational Technologymentioning
confidence: 99%
“…Critical thinking was found to increase both in an EFL class offered in a traditional setting, but much more so in a Facebook-enhanced one (dppc2 = 0.545) (Morris, 2008), after students were trained to answer questions developed on a revised Bloom's Taxonomy scale (Pattanapichet & Wichadee, 2015). Installing courseware in the laboratory to enhance teacher-centered instruction, led students in the study by Tsai (2012) to develop more critical thinking skills in the sense that they reported to have improved "abilities of thinking, analysis and problem-solving" (p. 56).…”
Section: Cognitive Engagement and Educational Technologymentioning
confidence: 99%
“…As far as the results of studies are concerned, a number of papers reported a more positive impact on learning processes and participation when Facebook was compared with traditional LMS such as Moodle or Blackboard (Chang & Lee, ; Chen, ; Daclan, ; Gregory et al, ; Hurt et al, ; Kent, ; Kurtz, ; Lateh, ; Lin et al, ; Meishar‐Tal et al, ; Miller, ; Parmaxi & Zaphiris, ; Pattanapichet & Wichadee, ; Sutcliffe & Alrayes, ; Tananuraksakul, ). In a qualitative study carried out in teacher education, Meishar‐Tal et al () found that students perceived the Facebook group as a dynamic and collaborative learning environment that supported mutual help and social consolidation.…”
Section: Formal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 99%
“…For them, Web 2.0 tools and social media can boost their learning from various aspects as is also suggested by the previous literature (e.g. Al-Rahmi, Othman & Musa, 2014;Pattanapichet & Wichadee, 2015).…”
Section: Resultsmentioning
confidence: 53%